Levels of Facebook usage among Al-Mustaqbal University students /Department of Media and the results achieved. -Survey study - Abdulkadhim Mohammed Iswayyid, Lect (lark, 2024)
Social media platforms, especially the Facebook application, have become very popular among various segments of society. Because of its wide fame on the global level, it has become one of the most used sites in the world, as it has taken control of what was known in sociology as the third place.  Social media platforms, including the Facebook application, have attracted the attention of Iraqis greatly in recent decades through use and subscription.    This study aims to determine the level of use of the Facebook application by students of the Department of Mass Communication at Future University, and to know the motives for use and the satisfactions achieved as a result of use.This research is considered one of the descriptive analytical research. The researcher relied on the survey method and used a questionnaire form consisting of eleven questions that were distributed to the user audience, students of the Media Department, to collect information that achieves the research objectives.    The results of the research showed that males (46%) are more likely to use the Facebook application than females, with the percentage of females being (39%). Also, male students from the research sample are more free than females in practicing their lives by choosing the paragraph (all of the above) with a percentage of (49.21%), while the paragraph (at home) came in first place with a percentage of (42.86%). The use of the Facebook application was identical (depending on circumstances) for males and females, as the ranking according to circumstances came in first place for males, with a percentage of (75%) and a percentage of (71%) for females. The students of the Mass Communication Department use Facebook incorrectly and have moved away from positive use in benefiting from this technology to develop themselves and increase their information. The paragraph (messages and conversations in audio and video) came in first place for males, with a number of repetitions (68) and a percentage of (15.01%), while the paragraph came in first place for males, with a number of repetitions (68) and a percentage of (15.01%). (Chat) ranked first with a number of repetitions (73) and a percentage of (18.53%). It became clear that there were statistically significant differences at a significant level (0.01) between the motives for exposure and the gender (male - female).
Keywords: Levels usage Facebook the results achieved